The Effect of Compensation on the Performance of KSPPS Hudatama Semarang Employees - Dyah Purwaningrum; Sutaat Sutaat (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
KSPPS Hudatama Semarang is an independent business organization that has activities to develop various productive business activities to improve the quality of economic activities carried out by small communities and entrepreneurs. Providing appropriate compensation is one way that can be used to improve performance for employees to achieve the desired performance of the company. At work, Compensation is very important for employees because the size of the compensation is a measure of employee performance. Employees always expect a more adequate income. Based on this view, researchers are interested in conducting research related to compensation for employee performance through the title